2019
DOI: 10.1038/s41598-019-46929-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Skeletal Muscle in Aged Mice

Abstract: Sarcopenia is the age-induced, progressive loss of skeletal muscle mass and function. To better understand changes in skeletal muscle during sarcopenia, we performed a metabolomic analysis of skeletal muscle in young (8-week-old) and aged (28-month-old) mice by using capillary electrophoresis with electrospray ionization time-of-flight mass spectrometry. Principal component analysis showed clear changes in metabolites between young and aged mice. Glucose metabolism products were decreased in aged mice, specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 28 publications
10
71
1
Order By: Relevance
“…Aging has been shown to increase skeletal muscle phospholipids, as Schunk et al have shown, using 31 P‐MRS, phosphomonoester content, an in vivo readout of PC and PE is elevated in muscle of older adults (Schunk et al, 1999). Additionally, recent evidence by Uchitomi and colleagues has shown differential phospholipid composition in aged rodent muscle, with the majority of phospholipids increased in aged skeletal muscle in comparison to younger counterparts (Uchitomi et al, 2019). The changes in phospholipid composition were associated with reduced type IIb myofiber size in aged muscle (Uchitomi et al, 2019), which is similar to our findings revealing a negative association between phospholipids (PC, PE, and PG) with muscle volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging has been shown to increase skeletal muscle phospholipids, as Schunk et al have shown, using 31 P‐MRS, phosphomonoester content, an in vivo readout of PC and PE is elevated in muscle of older adults (Schunk et al, 1999). Additionally, recent evidence by Uchitomi and colleagues has shown differential phospholipid composition in aged rodent muscle, with the majority of phospholipids increased in aged skeletal muscle in comparison to younger counterparts (Uchitomi et al, 2019). The changes in phospholipid composition were associated with reduced type IIb myofiber size in aged muscle (Uchitomi et al, 2019), which is similar to our findings revealing a negative association between phospholipids (PC, PE, and PG) with muscle volume.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent evidence by Uchitomi and colleagues has shown differential phospholipid composition in aged rodent muscle, with the majority of phospholipids increased in aged skeletal muscle in comparison to younger counterparts (Uchitomi et al, 2019). The changes in phospholipid composition were associated with reduced type IIb myofiber size in aged muscle (Uchitomi et al, 2019), which is similar to our findings revealing a negative association between phospholipids (PC, PE, and PG) with muscle volume. While in contrast to recent reports that showed reducing PE levels in skeletal muscle by inhibiting key phospholipid synthesis pathways (phosphatidylserine decarboxylase) results in muscle atrophy (Heden et al, 2019; Selathurai et al, 2019), our findings and those by Uchitomi et al (2019) reveal that age‐induced muscle atrophy may be linked to elevated phospholipids levels in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…These structures are also found in muscle of aged mice (Lin et al, 2018), suggesting that Zmynd17deletion accelerates muscle senescence. It has been reported that type IIb fibers, but not IIx or IIa fibers, are markedly affected by aging, which is related to muscle atrophy, known as sarcopenia (Holloszy et al, 1991;Uchitomi et al, 2019). Presumably, type FIGURE 4 | Voluntary exercise attenuates mitochondrial abnormalities of Zmynd17-KO;PGC1α-transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, sarcopenic declines in skeletal muscle mass typically manifest in the fourth decade of life (51,52). The onset of sarcopenia in mice, on the other hand, has not been welldocumented (53,54), and studies of sarcopenia in animal models often exclude the oldest-old cohort (53,55,56). We found that decreased muscle mass and functiontwo of the classical markers of sarcopeniabecome prominent in the oldest-old group for both male and female mice, whereas muscle declines in old mice are relatively modest.…”
Section: Discussionmentioning
confidence: 99%